2021
DOI: 10.1007/s40273-021-01078-7
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Working at Home and Time Allocation Between Paid Work, Unpaid Work and Leisure Activities During a Pandemic

Abstract: Background and Objective The COVID-19 pandemic and the measures taken by governments to contain it have affected many aspects of the daily lives of citizens. This study aimed to describe changes in the productivity of paid work and time allocation to paid and unpaid work and leisure resulting from working at home during the pandemic. Methods A sample of 851 people from the Netherlands who had paid work (≥ 24 h/week) and worked at least 4 hours per week extra at home bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Multidisciplinary literature has revealed that job productivity, well-being and work-life balance are key factors when exploring the impact of remote technology on employees, managers and firms, especially if the work is managed by objectives and performance-based (Sharafutdinova et al , 2022; Leonardi, 2020; Mingardo et al , 2020). Following literature and data collected by Eurofound (2020) the positive aspects of remote working can be summarized as follows: increased productivity (Abdellatif, 2021; Abujarour, 2021; Awada et al , 2021; Guler et al , 2021; Huls et al , 2021; Nuur et al , 2021); greater autonomy (Wong et al , 2021); and improvement in flexibility (intended as the possibility to work from different locations without the limitations due to office-based hours and risks related to displacement and crowding) (Kniffin et al , 2021; Troll et al , 2021). …”
Section: Organizational and Managerial Aspects Learning Experiences I...mentioning
confidence: 99%
See 2 more Smart Citations
“…Multidisciplinary literature has revealed that job productivity, well-being and work-life balance are key factors when exploring the impact of remote technology on employees, managers and firms, especially if the work is managed by objectives and performance-based (Sharafutdinova et al , 2022; Leonardi, 2020; Mingardo et al , 2020). Following literature and data collected by Eurofound (2020) the positive aspects of remote working can be summarized as follows: increased productivity (Abdellatif, 2021; Abujarour, 2021; Awada et al , 2021; Guler et al , 2021; Huls et al , 2021; Nuur et al , 2021); greater autonomy (Wong et al , 2021); and improvement in flexibility (intended as the possibility to work from different locations without the limitations due to office-based hours and risks related to displacement and crowding) (Kniffin et al , 2021; Troll et al , 2021). …”
Section: Organizational and Managerial Aspects Learning Experiences I...mentioning
confidence: 99%
“…increased productivity (Abdellatif, 2021; Abujarour, 2021; Awada et al , 2021; Guler et al , 2021; Huls et al , 2021; Nuur et al , 2021);…”
Section: Organizational and Managerial Aspects Learning Experiences I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Validating such measures for this purpose is, of course, important, as is a better understanding of compensation mechanisms and multiplier effects in the context of working from home more often. Moreover, it will be interesting to investigate, like in Huls et al [ 2 ], the determinants of productivity at home, including family composition, working space, type of work, etc. Finally, if in the post-corona era presenteeism becomes more and absenteeism less prominent, this may also have consequences for valuation methods, for instance, whether and how replacement, as assumed in the friction cost method (e.g.…”
Section: Methods Presently Used For Measuring Presenteeismmentioning
confidence: 99%
“…This change was facilitated by digital communication tools that rapidly became part of everyday life (also for academics, like it or not) and meant adaptation to a new way of working for many involved. The productivity of people working from home, relative to that in a formal workplace, especially during lockdowns and with little time to adjust, is a relevant and interesting issue to study in its own right, as highlighted in, for instance, Huls et al [ 2 ]. Such studies can also be relevant in investigating the costs and benefits of different policy interventions related to reducing infection rates during a pandemic.…”
Section: Introductionmentioning
confidence: 99%